Toxicity Analysis: A Collection of Case Studies and Drug Management Strategies - Samsul, Erwin; Khotimah, Ika; Harludi, Theodora Jane; Purba, Gmelina Adelia Putri; Wahyuda, Aji Arda Nur; Sudarma, Mahatma Setya; Rajo, Nur Wulan Mas; Rahma, Saina Cintami Abdila; Ardhito, Willy (Journal of Pharmaceuticals and Natural Sciences, 2025)
Narcotics, Psychotropics, and Addictive Substances (NAPZA), are any compound or drug that can alter the central nervous system and behavioural patterns, that can also cause an addiction. Narcotics and psychotropics in itself can be categorized into 3 categories of narcotics, and 4 categories of psychotropics, based on their use as a medication and the possibility of an addiction. Since NAPZA can alter the central nervous system, the possibility of their toxicity needs more attention. This study is done to review the handling and the mechanism of toxicity of NAPZA. We used the narrative review method to gather information from various sources, including 3 websites, 1 book, 7 national articles, and 22 international articles that were published in the time span of 2014 to 2024. From the 11 cases of NAPZA toxicity, 4 were caused by narcotics, 4 by psychotropics, and 3 by addictive substances, with most cases were of drug misuse by the productive population. The main handling of narcotics toxicity were to secure the breathing function, oxygen supplementation, and the use of Naloxone as an antidote. While psychotropics and addictive substances poisoning were handled with the use of benzodiazepines, hemodialysis, or to increase the rate of drug elimination in the plasma.